Retorno ao trabalho e transtornos mentais e do comportamento: um estudo com servidores públicos municipais - Toniolo, Ana Carolina (Universidade Federal de São Carlos, 2014)
In Brazil, the Mental and Behavioral Disorder ranks third in number of sickness benefits provided by the National Institute of Social Security (INSS) and thus illustrate the importance of further research on the topic. The aim of this study was to know the process of return to work of municipal workers who were turned away by mental and behavioral disorders, received sickness benefit (for incapacity) and returned to work activities. Participants were seven employees of a Municipality in the State of Sao Paulo, who managed to return to work activities after being away from work for 30 days or more with a primary diagnosis of Mental and Behavioral Disorders (CID F from CID-10) in the period January 2008 to December 2012. Data collection happened in the period December 2012 to March 2013 and it accomplished through filling out a personal information and professional protocol related to the removal process and return to work and the application of a semi-structured interview which addressed questions about the process of removal and return to work. For data analysis, the technique used was Thematic Analysis. The results showed that the participants were unanimous in considering their families as the main source of support in the process of return to work activities. Regarding the reasons that led to the illness and consequent removal from work, some participants reported poor relationship with superiors and coworkers. Nevertheless, a good relationship with management and co-workers appeared to aid in the process of returning to work. The physical environment, inadequate and precarious working conditions were identified as facilitators for mental illness in workers. Participants signaled suggestions about changes in their work environments, which could make them less sick prone, and more appropriate and favorable for good employee performance. For most of the study participants there is no difference in the meaning of work in their lives prior to removal and after returning to work. The work takes on different meanings in the lives of the participants related to personal fulfillment and enjoyment, social function, means of support and space for socializing. Although all participants had undergone expert care of the INSS, none received any information or indication on the Vocational Rehabilitation Program of the INSS. It is expected that this research will contribute to the strengthening of the local network of health care worker and bring enlightenment about reinsertion of these people into the labor market and the assurance of their rights.
Keywords: Terapia ocupacional; Trabalho; Transtornos mentais; Retorno ao trabalho; Readaptação ao emprego; Work; Mental disorders; Return to work; Readaptation to work; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL